Etika Bisnis Islam Dalam Jual Beli Di Marketplace - Ayu Maretta Maharani; Ulfatul Khasanah (Journal of Islamic Economics and Finance, 2023)
This research discusses marketing that occurs in the existing Shopee Marketplace in connection with the current implementation of Islamic business ethics, Shopee sellers must maintain integrity and honesty. The phenomenon that occurs is honesty, where the seller displays an accurate and honest product description. using primary and secondary data methods. Informants in this research include sellers at the Shopee Marketplace in the city of Sampang and outside the city of Sampang. Using an approach with qualitative research methods. To check and test data validity techniques, use the Triangulation method. Data analysis in this research was carried out through the stages of data reduction, data presentation, and drawing conclusions as the final goal. The research results show that in Islamic Business Ethics in marketing on the Shopee Marketplace it is important to prevent practices of manipulation, intimidation or immoral behavior towards buyers which include: Unity, Balance, Free Will, Responsibility Responsibility), and Truth. The conclusion in this research is that the implementation of Islamic Business Ethics in marketing activities at the Shopee Marketplace has not been fully implemented in its entirety. The importance of applying Islamic Marketing Ethics by interacting with sellers in the marketing process to provide a deeper understanding.